Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)